ARTISANAL FISHING AND POVERTY IN THE COMMUNITIES NEAR THE NICOYA´S GULF - Fernández Carvajal, Doris (2013)
This article describes the critical situation of traditional fishing at the Nicoya Gulf and how it affects the poverty conditions of some families in the communities of Morales, Costa de Pájaros and Manzanillo de Chomes in the Puntarenas province. The article is structured in two parts: first, it shows some data regarding the decrease in the main fishing resources in the area, as well as other elements that enable a more comprehensive perspective on the issues depicted. The second part shows the impact that this situation has over the life of a group of forty women and their families.